2010
DOI: 10.1038/bmt.2009.358
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic SCT in children with Griscelli syndrome: a single-center experience

Abstract: In total, 11 consecutive pediatric patients with Griscelli syndrome (GS) type 2, who received allogeneic hematopoietic SCT (aHSCT) at our center between 1993 and 2007, were reviewed. The median age at transplantation was 8.2 months (range, 4-36.3 months) and the median time from diagnosis to transplantation was 3.7 months (range, 1.4-19.5 months). Seven patients developed an accelerated phase and were treated with chemotherapy before transplantation. At the time of transplantation, all patients were in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…These studies [Horne et al , 2005 ( n = 86); Ouachee‐Chardin et al , 2006 ( n = 48); Baker et al , 2008 ( n = 91)] observed 3–5 year probabilities of survival ranging from 49% to 64% (Table I). Recent observations of predominantly Italian, Japanese, or Korean patients are similar (Cesaro et al , 2008; Ohga et al , 2010; Yoon et al , 2010), and experiences with Chediak–Higashi syndrome (Eapen et al , 2007) and Griscelli syndrome (Pachlopnik Schmid et al , 2009; Al‐Ahmari et al , 2010) have also been reported (Table I). Deaths in most series were predominantly before day +100, and related to early transplant‐related complications including non‐engraftment, hepatic, pulmonary toxicity, pneumonia, interstitial pneumonitis, bronchiolitis obilterans, idiopathic pneumonia syndrome, infections, organ failure, haemorrhage and graft‐ versus ‐host disease (GVHD), or to HLH.…”
Section: The First Steps: Myeloablative Conditioning (Mac) Regimens Fmentioning
confidence: 56%
“…These studies [Horne et al , 2005 ( n = 86); Ouachee‐Chardin et al , 2006 ( n = 48); Baker et al , 2008 ( n = 91)] observed 3–5 year probabilities of survival ranging from 49% to 64% (Table I). Recent observations of predominantly Italian, Japanese, or Korean patients are similar (Cesaro et al , 2008; Ohga et al , 2010; Yoon et al , 2010), and experiences with Chediak–Higashi syndrome (Eapen et al , 2007) and Griscelli syndrome (Pachlopnik Schmid et al , 2009; Al‐Ahmari et al , 2010) have also been reported (Table I). Deaths in most series were predominantly before day +100, and related to early transplant‐related complications including non‐engraftment, hepatic, pulmonary toxicity, pneumonia, interstitial pneumonitis, bronchiolitis obilterans, idiopathic pneumonia syndrome, infections, organ failure, haemorrhage and graft‐ versus ‐host disease (GVHD), or to HLH.…”
Section: The First Steps: Myeloablative Conditioning (Mac) Regimens Fmentioning
confidence: 56%
“…In the United States, transplant if routinely offered in advance of the accelerated phase of classic disease. In a single-center review of the use of hematopoietic stem cell transplantation (HSCT) in Griscelli syndrome type 2 [25], many patients continued to suffer major neurological deficits after HSCT, leading the authors to suggest that transplanting these patients prior to the accelerated phase could be beneficial. The presence of neurodegenerative signs appearing in classical CHS patients many years after BMT suggests that neurodegeneration may be related in part to defective lysosomal trafficking and vacuolar dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated phase of GS2 is another form of FHL and is fatal without standard chemotherapy and immunosuppression (see SS 121). [445][446][447] Hermansky-Pudlak syndrome. Summary statement 118.…”
Section: Diseases Of Immune Dysregulationmentioning
confidence: 99%